Is There any Improvement in Total Factor Productivity Growth of Indian Pharmaceutical Industry after TRIPS Agreement? : Evidence from Biennial Malmquist Index - Dipyaman Pal; Chandrima Chakraborty; Arpita Ghose (The Central European Review of Economics and Management (CEREM), 2018)
Aim: Indian Pharmaceutical Industry (IPI) has undergone a massive makeover-from a modest beginning of "process patents regime" in the seventies to a modern and WTO compatible regime under the Trade Related Intellectual Property Rights System (TRIPS) in 2005. This paper estimates Total Factor Productivity Growth (TFPG) of Indian Pharmaceutical Industry (IPI) using firm level data from 2000 to 2013.~Design / Research methods: We have used nonparametric approach of Data Envelopment Analysis (DEA) using Biennial Malmquist Index.~Conclusions / findings: The results of estimation suggest an increase in overall TFPG of IPI after TRIPS agreement and also those vertically integrated firms involved in both bulk drugs production and formulation activities are less productive compared to firms that are involved in production of only bulk drug or formulation activity.~Originality / value of the article: This paper examines whether productivity of IPI has increased after 2005 i.e. after the period of TRIPS, by estimating TFPG for two sub-periods, i.e., from 2000 to 2005 and 2006 to 2013.~Implications of the research: The decomposition of TFPG suggests that for overall period 2000-2013, scale changes are the most important factor causing the productivity changes and among the other two alternative sources of TFPG, efficiency change dominates over technical changes. For the sub-period 2006-2013, the improvement in the scale efficiency may push the firms to a higher TFPG, whereas for 2000-2005 the better utilization of factors of production is the main driver of TFPG. A second stage panel regression suggests that R&D expenditure, Marketing expenditure, Market size, Capital-Labour ratio, import intensity and export intensity have positive and significant influence on TFPG.
Keywords: L65; C14; C33; 330; Total Factor Productivity Growth (TFPG); TRIPS; Indian Pharmaceutical Industry; Data Envelopment Analysis (DEA); Biennial Malmquist Index